Immediate eﬀect of anti-pronation foot taping on myoelectric activity of knee muscles in patellofemoral pain syndrome: a randomised controlled trial - Saleh, Omaima E.; Swief, Radwa E.; Abdallah, Amira A.A. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. There is lack of studies on the eﬀect of anti-pronation foot taping on the myoelectric activity of knee muscles. The purpose of this study was to investigate the immediate eﬀect of anti-pronation foot taping on the myoelectric activity of the vastus medialis oblique and vastus lateralis muscles and their activity ratio in patellofemoral pain syndrome.Methods. Twenty-six female patients were randomised into two equal groups. The study group A used augmented low Dye taping, while the control group B did not. The patients’ age, weight, height and BMI ranged between 18–31 years, 50–73 kg, 1.53–1.72 m and 20–25 kg/m². All patients were evaluated twice; pre- and immediately post-foot taping (pre-test post-test control group design). Normalised data of the myoelectric activity of the knee muscles were recorded using a Neuro-EMG-Micro device during stair climbing and single leg mini-squat.Results. The ﬁrst 2 × 2 Mixed Design MANOVA revealed that the myoelectric activity of the vastus medialis oblique decreased signiﬁcantly (p = 0.001) during both stair climbing and single leg mini-squat in group A post-taping compared with pre-taping. Similarly, the activity of the vastus medialis oblique decreased signiﬁcantly (p = 0.019) post-taping in group A compared with group B during single leg mini-squat. The second 2 × 2 Mixed Design MANOVA test revealed that the activity ratio decreased signiﬁcantly (p = 0.001) post-taping compared to pre-taping in group A during stair climbing.Conclusions. Anti-pronation foot taping reduces the activity of the vastus medialis oblique during stair climbing and single leg mini-squat.
Keywords: anterior knee pain; vastus medialis oblique; myoelectric activity; augmented low Dye taping; vastus lateralis